THE EFFECT OF ADDITION GREEN INHIBITOR D-GALACTOSE ON CORROSION RATE OF ALUMINUM ALLOY 5052 IN SULFURIC ACID (H2SO4) MEDIA - Muhajirin Muhajirin; I. G. A. Arwati; S. Hartati; H. Hakim; Alfian Noviyanto; Arramel Arramel; T. Zakly (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2022)
Aluminum alloy 5052 (Al5052) is one of the metals used as a bipolar plate in a Proton Exchange Membrane Fuel Cell (PEMFC) due to has its light mass and being easy to form, and, has high conductivity and resistivity properties. This material is prone to corrosion and current knowledge to protect its surface is currently lacking. The product of PEMFC produces electrical energy, hot steam (313 – 353 K), and water. These conditions have an impact on the degraded bipolar plate caused by the acidic nafion membrane. This increases the risk of corrosion on the cathode side of the bipolar plate. Coating with a green inhibitor using the electrophoretic deposition technique (EPD) is one way to deal with the corrosion that occurs. The analysis method used electrochemical with potentiodynamic polarization techniques, electrochemistry impedance spectroscopy (EIS), Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). In this study, green inhibitor D-galactose was used with a concentration of 0.5 – 1.5 g and an, EPD time of 15 – 45 minutes in 0.5 M sulfuric acid (H2SO4) media pH 1-4. Potentiodynamic polarization analysis at the lowest corrosion current value (Icorr) at demonstrates (the inhibitor concentration of 1.5 g with an and EPD time of 45 minutes) resulted corrosion rate of Al5052 before EPD was 0.0075 mmPY while the corrosion rate of Al5052 after EPD was 0.0041 mmPY with (inhibitors efficiency 45.2%). The FTIR spectrum, broad peak appeared in the range of 3000-3600 cm-1, which refers to the formation of hydrogen bonding of hydroxyl group. Methyl group of D-galactose also appear on 2918 cm-1 and 2850 cm-1 which attributed to =CH2 asymmetric stretch and −CH3 symmetric stretch, respectively. Carbonyl group on 1500 – 1700 cm-1 represent C=O bond of amide, and aldehyde. Peak 1097 – 1035 cm-1 which attributed to C-O were connected to the secondary and primary alcohols. The resistance value for Al5052 before and after EPD are 1.2 kΩ/cm2 after and 2.2 kΩ/cm2, respectively. Here we find that the resistance increases with the increasing concentration and time of EPD. The results cross section Al5052 within average 29.8 μm, and morphology with SEM Al5052 before EPD showed pitting corrosion. On the other hand, the image of Al5052 inhibitor coating 1.5 gr with EPD of 45 minutes shows a smooth surface and visible black lumps, suggesting Al5052 is successfully reduced a corrosion rate by the D-galactose. Our simple and robust method inferred a protection route towards a viable and physically stable green inhibitors.